The Ice Chronicles : The Quest to Understand Global Climate Change - Mayewski, Paul A. (Book collections on Project MUSE., 2002)
An exciting account of revolutionary new discoveries for understanding the earth's climate, and their implications for future scientific research and global environmental policy. -- from publisher description.